2011
DOI: 10.1371/journal.pone.0022612
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Attention in Binocular Rivalry: Electrophysiological Evidence

Abstract: During binocular rivalry visual consciousness fluctuates between two dissimilar monocular images. We investigated the role of attention in this phenomenon by comparing event-related potentials (ERPs) when binocular-rivalry stimuli were attended with when they were unattended. Stimuli were dichoptic, orthogonal gratings that yielded binocular rivalry and dioptic, identically oriented gratings that yielded binocular fusion. Events were all possible orthogonal changes in orientation of one or both gratings. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 44 publications
6
20
0
Order By: Relevance
“…The behavioral data showed that the mean perception dominance duration was variable between subjects and consistent with the previous studies using similar stimuli [14], although an EEG study reported a shorter perception dominance duration using rotating gratings as stimuli [26]. Interestingly, we noticed that the worst performance of our brain states classifier was obtained from subjects 5 and 6, who experienced shorter mean perception durations (respectively 2.57 s and 1.78 s); we speculate that it may be harder to decode a signal when perception changes are too quick.…”
Section: Discussionsupporting
confidence: 89%
“…The behavioral data showed that the mean perception dominance duration was variable between subjects and consistent with the previous studies using similar stimuli [14], although an EEG study reported a shorter perception dominance duration using rotating gratings as stimuli [26]. Interestingly, we noticed that the worst performance of our brain states classifier was obtained from subjects 5 and 6, who experienced shorter mean perception durations (respectively 2.57 s and 1.78 s); we speculate that it may be harder to decode a signal when perception changes are too quick.…”
Section: Discussionsupporting
confidence: 89%
“…There is no necessary contradiction here if it is assumed that Lamme’s two stages operate in parallel. Perhaps what is surprising in the light of our results is just how late the predictive activity is, at the time of the second, and not the first (100 ms after an event) major ERP component to have been shown to be a neural correlate of consciousness in binocular rivalry [20], [64], [65] and in masking [111].…”
Section: Discussionmentioning
confidence: 61%
“…We re-referenced the EEG data offline to the linked earlobes. We did this to allow comparison with earlier work on multistable visual phenomena that also used linked ears [40], [41], [42], [43], [64], [65], [82], [83]. We applied a 0.3–35 Hz bandpass filter (Kaiser windowed sinc FIR filter, 1857 points, Kaiser window beta 5.65326) to the data before analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of a preserved marker of switches in V1 is consistent with recent optical imaging work in monkeys, showing that an alternating pattern of V1 activity in response to rivalry stimulation remains even under general anesthesia (Xu et al, 2016). In potentially related work, Roeber, Veser, Schröger, & O'Shea, 2011 measured event-related potentials (ERPs) and discovered a difference in response to rivalrous stimuli compared to non-rivalrous stimuli; a difference that remained even if the stimuli were unattended (also see Katyal, Engel, He, & He, 2016). This may suggest similar treatment of attended and unattended rival stimuli by the visual system (i.e.…”
Section: Introductionmentioning
confidence: 99%